Factor influencing child marriage in Tanjung Terdana Village 2020-2022 - Sholehah, Annida; Destariyani, Elvi; Damarini, Susilo; Elly, Nur; Widiyanti, Desi (Alma Ata University Press, 2024)
Background: Child marriage is a marriage that takes place at an age under 19 years that can threaten life and health. Indonesia's child marriage rate is ranked 7th globally and is ranked 2nd in ASEAN. Child marriage brings more harm than good, it tarnishes children rights in so many aspects including the health rights. It can affects children’s growth and development, especially females under the age of 19 can experience such serious injuries considering the reproductive organ is still immature for them to have sex, let alone pregnant and give birth. Apparently, the child marriage can be influenced by many factors, such as culture, socio-economic and environment. Altough the marriage age has been regulated in laws, the number of child marriage is still arrising.Objectives: This study aims to determine the factors that affecting child marriage in Tanjung Terdana Village, Pondok Kubang District, Central Bengkulu Regency.Methods: The research method is analytic observational with a cross-sectional design. The population is a reproductive age women that married in KUA Pondok Kubang distric in 2020-2022. Samples were taken by a total sampling technique of 31 reproductive age women, and data was collected using a questionnaire. Data analysis used a chi square, fisher’s exact and logistic regression.Results: The results indicate that culture, environment and sosio-economic influence the child marriage with a value (p-value) <0,05, where the most dominant factor is culture.Conclusions: The health workers can work and collaborate cross-sectorally with the local community leaders in order to develop counseling and education programs about reproductive health in the community, especially among adolescents.